Uma revisão sistemática sobre a eficácia da radiação ultravioleta como agente germicida - Medeiros, Fernanda Costa de (2023)
Faced with the pandemic scenario in which we are inserted, the search for different means of prevention has been one of the main subjects studied worldwide. In this way, it reminded us of the importance of the process of disinfection and environmental sanitation in internal areas, as well as clinics and hospitals. Within this context, a survey of works was carried out that used ultraviolet-C radiation (UVC) as an effective physical agent to inactivate both the SARS-CoV-2 virus and other microorganisms in different environments and surfaces. In this present research, we carried out a survey of studies carried out mainly in the last 3 years (2019-2022), in order to find what is most up-to-date from a technological point of view. The main search engines for these works were the Web of Science database, Science Direct, PubMed, and the CAPES Periodicals Portal. Using search strategies, approximately 2,137 records were identified, including articles, dissertations, and theses, which were based on UVC radiation as a means of inactivating pathogenic agents. The use of different technologies and radiation doses was verified. The inactivation of microorganisms (fungi, bacteria, and viruses) including the SARS-CoV-2 virus was verified, reaching a range of up to approximately 99.999% in its inactivity, where such results were influenced by the experimental conditions in question. These consequences show evidence of the effectiveness of UVC radiation as an important technological resource to combat SARS-CoV-2. Therefore, in this perspective, this work is careful to provide an overview of the significant role in which this radiation played in the immediate process of combating the COVID-19 pandemic, such as redirecting existing technologies with the perspective of prevention and combat in medium /long term to possible pandemics of this caliber.